KRAS in Pancreatic Cancer - Agarwal, Archana; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is one of the most feared malignancies. The most common form of pancreatic cancer is adenocarcinoma arising from the ductal epithelium. KRAS is the most common oncogene that has been found to be mutated. However, targeting KRAS directly has been difficult. We do not know a lot about the relationship between KRAS and other signaling pathways. At the same time, little is known about the non KRAS mutated or wild type (WT) tumors. Most of the data that we have as far, as mutational status is concerned, has been obtained from the tumor itself and not from metastatic lesions. In this review, we discuss two abstracts (Abstracts #e15214 and #e15207) published in conjunction with the 2014 ASCO Annual Meeting. These discuss the relationship between KRAS and other signaling pathways and the differences between mutated KRAS and WT tumors. The studies found low rate of KRAS mutation in cells obtained from ascitic fluid. While the studies are small, these are novel findings that are worth exploring further. They increase our understanding of the biology of the disease and take us a step closer to treating this deadly malignancy. Image: KRAS mutation and concordance rates with primary tumor.